The Kingfisher book of how things work - Paeker, Steve (Kingfisher, London, 1990)
Presenting its subject in a question and answer format, this book aims to help the young and enquiring mind discover the mysteries which operate examples of technological complexity such as the car, can opener, aeroplane or tree.